Java Collections - Zukowski, John (Apress, 2012)
When learning a new computer programming language, one of the first things you tend to ask is how to work with large groups of data. This topic is often covered in the second course of the standard curriculum for Computer Science as part of a class typically called Data Structures. If you were to look at the class syllabus, you'd likely see topics such as linked lists, queues, stacks, and binary trees, among many other data structures. In Java, these structures are part of the Java Collections Framework.í